2021
DOI: 10.1021/jacsau.1c00469
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Methane with Oxygen to Produce Hydrogen Catalyzed by Triatomic Rh3 Cluster Anion

Abstract: Metal catalysts, especially noble metals, have frequently been prepared upon downsizing from nanoparticles to subnanoclusters to catalyze the important reaction of partial oxidation of methane (POM) in order to optimize the catalytic performance and conserve metal resources. Here, benefiting from mass spectrometric experiments in conjunction with photoelectron spectroscopy and quantum chemical calculations, we successfully determine that metal cluster anions composed of only three Rh atoms (Rh 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…27,28 However, in part due to scalability challenges, the elucidation of catalytic intermediates remains challenging and relies heavily on computational modeling. 29,30 Our group introduced a family of molecular clusters, M3 (M3Co6Se8L6; M = Fe, Co, Zn, Sn; L = Ph2PNTol -), 16,[31][32][33][34] that incorporate three chemically addressable edge sites (M) on the surface of a Co/Se cluster core, a construct reminiscent of edgedoped transition metal dichalcogenide nanoflakes (Figure 1). 6,7,11 Hemilabile edge-support interactions stabilize the three edge sites in protected low-coordinate states, 31 positioning them to function as catalytically active sites and enabling the systematic study of electronic metal-support interactions, 35 as well as allosteric 34 and multi-site dynamics on the cluster surface.…”
mentioning
confidence: 99%
“…27,28 However, in part due to scalability challenges, the elucidation of catalytic intermediates remains challenging and relies heavily on computational modeling. 29,30 Our group introduced a family of molecular clusters, M3 (M3Co6Se8L6; M = Fe, Co, Zn, Sn; L = Ph2PNTol -), 16,[31][32][33][34] that incorporate three chemically addressable edge sites (M) on the surface of a Co/Se cluster core, a construct reminiscent of edgedoped transition metal dichalcogenide nanoflakes (Figure 1). 6,7,11 Hemilabile edge-support interactions stabilize the three edge sites in protected low-coordinate states, 31 positioning them to function as catalytically active sites and enabling the systematic study of electronic metal-support interactions, 35 as well as allosteric 34 and multi-site dynamics on the cluster surface.…”
mentioning
confidence: 99%
“…The reactions of positively charged bare tantalum clusters Ta n + ( n =1‐10) and oxygen deficient Ta n O m + ( m =1 and 2) clusters with CH 4 have been systematically investigated by a cryogenic ring electrode ion trap [12k,35,45,52] . It was found that the Ta 8 O 2 + cluster has the ability to catalyze the C−C coupling of two CH 4 to generate C 2 H 6 [35] . In contrast with the reaction mechanism of aforementioned Pd 2 O + system, the interaction of Ta 8 O 2 + with the first CH 4 generated a key carbene intermediate Ta 8 O 2 (CH 2 ) + , which directly coupled with another CH 4 yielding C 2 H 6 .…”
Section: Coupling Reactions Of Ch4 Moleculesmentioning
confidence: 99%
“…cluster catalyst of Rh 3 − was characterized at room temperature [35] . By using a TOF‐MS coupled with a double ion trap apparatus including two quadrupole mass filters (QMFs) and two linear ion trap reactors (LITs) that can mass‐select product ions and spatially separate two different substrates, the detailed elementary reactions have been clarified and the importance of the order to feed the reactants to promote catalytic conversion of CH 4 →2H 2 has also been revealed.…”
Section: Conversion Of Ch4 With O2 O3 and N2omentioning
confidence: 99%
See 2 more Smart Citations